2010
DOI: 10.1002/cncr.25535
|View full text |Cite
|
Sign up to set email alerts
|

International staging system and metaphase cytogenetic abnormalities in the era of gene expression profiling data in multiple myeloma treated with total therapy 2 and 3 protocols

Abstract: In this article, a triplexer is presented for three operation frequencies in GSM, based on stepped impedance resonators (SIR).SIR structures have some characteristics, such as low weight, little dimension, and the ability of providing filter behavior with different frequencies in same dimensions. To design the triplexer, bandpass filters of each output should be design first. Parallel connection of three filters together causes an extreme increase in insertion loss of each filter and also reflection of power t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…64,65 Thus, this treatment including tandem ASCT can achieve impressive results even in those patients with adverse cytogenetics. However, one must acknowledge that such results are achieved at the expense of treatment-related death rates of 5%.…”
Section: Single Versus Tandem Transplant?mentioning
confidence: 99%
See 1 more Smart Citation
“…64,65 Thus, this treatment including tandem ASCT can achieve impressive results even in those patients with adverse cytogenetics. However, one must acknowledge that such results are achieved at the expense of treatment-related death rates of 5%.…”
Section: Single Versus Tandem Transplant?mentioning
confidence: 99%
“…63 Furthermore, subgroup analyses showed that the adverse effect of del(17p13) or TP53 deletion on PFS and OS was significantly reduced with TT3. 64,65 Thus, this treatment including tandem ASCT can achieve impressive results even in those patients with adverse cytogenetics. However, one must acknowledge that such results are achieved at the expense of treatment-related death rates of 5%.…”
Section: Single Versus Tandem Transplant?mentioning
confidence: 99%
“…27,28 Of particular interest has been defining risk groups according to gene-expression profiling that, if validated by others, will allow a more rational use of therapies in myeloma patients to achieve the overarching goal of maximum benefit with minimum burden of therapy. 29 However, what remains to be determined is whether such intensive induction therapy and posttransplantation consolidation is warranted for all patients with myeloma, or if it should be relegated to patients with specific risk categories.…”
Section: Role Of Autologous Sctmentioning
confidence: 99%
“…However, deletion of chromosome17p is consistently associated with poor prognosis, even on extensive treatment with new agents. Gene expression profiling (GEP), array comparative genomic hybridization (aCGH), and single-nucleotide polymorphism (SNP) arrays have made it possible to characterize patterns of genetic aberration and alteration in MM cells in a more sophisticated manner [9][10][11]. In this review series, Johnson et al provide a comprehensive and informative review on the novel classification of MM based on GEP analyses and highlight the ''GEP70'' signature for defining the emerging molecular genetic subgroups closely associated with unique clinicopathological features and the treatment outcomes.…”
Section: Risk-stratification By Cytogenetic and Molecular Profilingmentioning
confidence: 99%